Hubungan Depresi Dengan Lama Pemenuhan Kebutuhan Tidur Pada Lansia Di Desa Mojokambang Bandarkedungmulyo Jombang - Ilya, Manzilatil (MEDICA MAJAPAHIT, 2012)
One of changes happened to elderly is change of sleep pattern. Cause of sleep disorder on elderly is depression. Research goal is to know relation between depression and time period of sleeping needÂ  accomplishment on elderly in Mojokambang village, Bandarkedungmulyo, Jombang. The research design is analytic with crossectional approach. Independent variable is depression and dependent variable is time period of sleeping needÂ  accomplishment. The populations are 86 people and samples are 70 people, with sampling random simpel technique analysis is pearson test with alfa 0,05. Based on research, known that (1) most elderly experience of heavy depressionÂ  and there isÂ  no one experience of light orÂ  heavy depression. (2) Most of elderly have time period of sleeping needÂ  accomplishment around 1-6 hours/dayÂ  and no lansia needs less than 1 hour/day. Result of research express that by pearson test, get P Value value is 0,000, whileÂ  value Î± is 0,05. because of P Value<Î± so Â Ho refused but H1 accepted, it means there is relation/between depression with have time period of sleeping need accomplishment on elderly in Countryside Mojokambang Bandarkedungmulyo Jombang. Â These fellingâs are physiologically stimulates the sensory system to tge midbrain level in formatio reticularis area, this state will instead stimulate the cerebral cortex and peripheral nervous system, subsequent reciprocal signalâs from the two areas will return to the reticular activation system, so that the system is still avtive or in other side elderly will know the state of siege or can not sleep. The factor that effect depression in the elderly are the economic status factor, and job beside factors other than emplyment or economic, depression is also influenced by education and merried status factor. Based onÂ  result of above research suggested to health providersÂ  toÂ  optomalize the counselling about theÂ  importantance of accomplishmen of sleep need and minimizeÂ Â  depressionÂ  , spreadsÂ  leaflet and involvesÂ Â  health cadre of elderlyÂ  in giving motivation and education for elderlyÂ  to get in Comprehensive Service Post forÂ  elderly regularly. Keywords : Depression, Sleeping Need, Elderly